Transformasi Teori Organisasi Klasik Ke Modern - Destia Henni; Widia Sukma; Nurhijjah Nurhijjah; Akdila Bulanov (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This paper aims to examine the transformation of organizational theory from classical approaches to modern and critical perspectives. Classical organizational theory emphasizes efficiency, formal structure, division of labor, and rationality in organizational management, as reflected in the ideas of thinkers such as Taylor, Fayol, and Weber. However, this approach is considered to have limitations as it pays less attention to human aspects and social dynamics within organizations. In response, modern organizational theory emerged by emphasizing the importance of human relations, open systems, and adaptation to the external environment. This approach views organizations as dynamic and complex systems influenced by interactions between individuals, groups, and their environment. Furthermore, critical organizational theory arises as a form of reflection and critique of power domination, inequality, and hidden ideologies within organizational practices. This perspective seeks to reveal power relations and promote more equitable social change within organizations. Thus, the transformation of organizational theory reflects a paradigm shift from a mechanistic approach to one that is more humanistic, adaptive, and reflective of social realities.